Diffusion tensor imaging and plasma immunological biomarker panel in a rat traumatic brain injury (TBI) model and in human clinical TBI - To, Xuan Vinh; Mohamed, Abdalla Z.; Cumming, Paul; Nasrallah, Fatima A. (Frontiers in Immunology, 2024)
Neuroinflammatory reactions contribute importantly to the pathology and longterm sequalae of traumatic brain injury (TBI) and may also mediate salutogenic processes that protect the brain, specifically with respect to integrity of white matter structures. To investigate these interactions, we applied a panel of inflammatory markers in blood samples collected rats following a controlled cortical impact/CCI) model of TBI, and used MR-based diffusion tensor imaging (DTI) to evaluate white matter integrity at 60 days following the injury. In a series of 15 patients, we similarly evaluated the inflammatory marker panel and DTI post-ICU discharge. We found time-dependent elevations in several immunological markers in the TBI rats, which were associated with preserved fractional anisotropy (FA) in white matter. Most notably TBI-induced increases in plasma levels of IL-1β, IL-6, G-CSF, CCL3, CCL5, and TNF-𝛼 were associated with higher white matter integrity as measured by FA. Corresponding results in the clinical cases concurred with respect to associations between inflammatory marker panel results in comparison to samples from healthy controls, and likewise with respect to a general association between increased inflammatory markers and preservation of FA in vulnerable white matter regions.We conclude that inflammatory markers in plasma samples collected after a TBI are ambivalent with respect to prediction of favourable outcome versus a progression to more pervasive pathology and morbidity.